The genus Vieira Navás (Neuroptera: Chrysopidae): a new species, a key to the species, and new geographic records - Sosa, Francisco; Tauber, Catherine A. (Zootaxa, 2017)
Vieira Navás is a small genus of Neotropical green lacewings in the tribe Belonopterygini. Here, a fifth species, Vieira flinti sp. nov., is described from Venezuela and Brazil. This species shares significant features with disparate members of the genus; thus the genus as a whole is now known to express a more continuous range of morphological variation than previously recognized. We present a key for identifying Vieira species and new geographic records for previously described species in the genus.